Convex endobronchial ultrasound bronchoscope may enhance visualization and diagnosis by respiratory physicians: Clinical image of an endoscopic ultrasound with bronchoscope - Suzuka Matsuoka; Yuki Takigawa; Ken Sato; Tomoyoshi Inoue; Hiromi Watanabe; Kenichiro Kudo; Akiko Sato; Keiichi Fujiwara; Takuo Shibayama (Respirology Case Reports)
Key message Herein, we present the detection of two cystic lesions via the transesophageal route using endobronchial ultrasound and emphasize the fact that understanding the anatomy may enhance the diagnostic yield.